Electrochemical studies and modifications of CVD diamond electrodes - Chen, L (2014)
CVD diamond possesses certain attractive electrochemical properties inter alia low background current, broad potential window, chemical inertness and resistance to electrocorrosion and fouling. As a consequence its use in various areas of electrochemistry, such as electrochemical sensing, wastewater treatment and electrocatalysis is being explored. Unfortunately, alongside these attractive features, bare CVD diamond electrodes, in common with all other electrode materials, cannot be effectively applied in all electrochemical systems of interest, since for example it may not display useful electrochemical activity for the redox process of interest. In these circumstances it may be possible to modify the electrode by addition of other chemical species to the surface, to introduce the relevant activity. One of the main aims of this thesis was therefore to investigate the properties of certain chemical modifications to the diamond electrode surface. A second aim was also to explore for the first time the use of a practically useful form of single crystal diamond, so-called heteroepitaxial diamond, in electrochemistry. The diamond electrodes used were boron-doped material grown by chemical vapour deposition. A range of electrochemical methods, including especially cyclic voltammetry, square-wave voltammetry, impedance spectroscopy and scanning electrochemical microscopy, were used to characterise electrode properties. Other physical methods employed included scanning electron and atomic force microscopy, X-ray photoelectron spectroscopy and dynamic light scattering techniques. The electrochemical properties of heteroepitaxial single crystal diamond were explored and compared to polycrystalline counterparts. The single crystal diamond electrode was found to show superior properties in terms of wide potential window, low background current and homogeneous activity across the electrode surface, coupled with resistance to fouling. Heterogenous electron transfer rate constants were found to be lower than normally found on polycrystalline diamond; this was attributed to reduced density of states and absence of functional groups. An electrochemical route to the preparation of diamond electrodes, modified by PrOx@Pt core-shell particles was demonstrated. It was observed that these electrode modifiers were far less susceptible to poisoning than bare Pt nanoparticles when used in the electrochemical oxidation of methanol. It was also shown that diamond electrodes with these core-shell particles deposited on them, displayed useful activity for the electrochemical oxidation of nitric oxide. The presence of the PrOx layer was shown to impart useful selectivity against the oxidation of interfering compounds such as nitrite and ascorbic acid, without the loss of sensitivity which normally occurs if nafion coatings are used instead. Basic electrochemical characterisation of the PrOx coating showed that the layer was chemically active and did not serve as a simple blocking layer when deposited on the electrode. The activity of Pt modified diamond electrodes for the oxidation of nitrite species was also studied. It was also shown that the addition of carbon black to a diamond electrode resulted in much enhanced electrochemical properties in the detection of riboflavin.